Groundless Land Claims: Systemic Failures in Land Tenure Rights Protection in Indonesia - Kobul Nugraha; Harmono Harmono (Jurnal Legisci, 2026)
Background. The phenomenon of baseless land claims in Indonesia is an the rise and can no longer be treated as an ordinary civil dispute. This practice often involves manipulating documents, pseudo-physical possession, and the use of legal loopholes to legitimize unauthorized claims. Aims. This study aims to analyze the practice of baseless land claims from a positive legal perspective, identify systemic failure factors in land law, and formulate an ideal legal protection model for legitimate landowners. Methods. The method used is normative juridical, with a legislative, conceptual, and case-based approach, supported by studies of primary and secondary legal materials. Result. The results of the study show that the practice of baseless land claims is a form of abuse of legal instruments supported by weaknesses in the institutional structure, gaps in the substance of the law, and a legal culture that has not supported integrity. On the other hand, legal protection for legitimate landowners has not been effective, either preventively through the land registration system or repressively through judicial mechanisms. Conclusion. Therefore, systemic reform is needed through the digitization and integration of land data, the strengthening of supervision and law enforcement, and the expansion of access to justice for the community. Implementation. This study emphasizes that groundless land claims are an indicator of the state's failure to ensure legal certainty regarding ownership rights, making comprehensive reform in land governance in Indonesia an urgent need.